The Islamic apologetics movement in social media: A framing analysis Bang Zuma's content on YouTube - Mukhroman, Iman; Napilah, Paridah (Jurnal Iman dan Spiritualitas, 2025)
This study explores the digital Islamic apologetics movement led by Bang Zuma as a case of contemporary religious activism shaped by the dynamics of social media platforms. Using a qualitative approach that integrates framing theory and social movement theory, the research examines how Bang Zuma’s YouTube content constructs theological narratives, mobilizes collective identity, and engages a transnational Muslim audience. Through diagnostic, prognostic, motivational, and bridging frames, his content not only challenges Christian theological positions but also builds a participatory interpretive community around Islamic identity. The study reveals that the movement’s growth is facilitated by post-Reformasi political openness, algorithmic amplification, and the increasing visibility of Islam in Indonesia’s digital public sphere. While its confrontational style risks reinforcing religious polarization, it also democratizes theological engagement by making complex debates accessible to a wider public. This research contributes to the understanding of digital religion by offering a nuanced account of how framing strategies intersect with algorithmic culture and political opportunity structures, while also suggesting pathways toward more constructive models of interfaith dialogue in the digital age.